The effect of process parameters and plate thickness on in-plane inherent deformations in T-joint fillet weld. Issue 5 (7th October 2020) - Tian, Liang; Luo, Yu
Abstract : Purpose: The purpose of this paper is to quantitatively investigate the effect of process parameters (including welding current, voltage and speed) and plate thickness on in-plane inherent deformations in typical fillet welded joint; meanwhile, the plastic strains remaining in the weld zone are also analyzed under different influencing factors. Design/methodology/approach: To achieve the purpose of this study, a thermal-elastic-plastic finite element (TEP FE) model is developed to analyze the thermal-mechanical behavior of the T-welded joint during the welding process. Experimental measurements have verified the validity of the established TEP FE model. Using the effective model, a series of numerical experiments are performed to obtain the inherent deformations under the conditions of different influencing factors, and then the calculation results are discussed based on the relevant data obtained. Findings: Through numerical simulation analysis, it is found that the longitudinal and transverse inherent deformations decrease with the increase of welding speed and plate thickness, whereas as the nominal heat input increases, the inherent deformations increase significantly. The longitudinal shrinkage presents a quasi-linear and nonlinear distribution in the middle and end of the weld, respectively. The plastic strains in the cross section of the T-joint also vary greatly because of the process parameters and plate thickness, but the maximum value always appears near the location of the welding toe, which means that this point faces a relatively large risk of fatigue cracking. The inherent deformations are closely related to the plastic strains remaining in the weld zone and are also affected by many influencing factors such as process parameters and plate thickness. Research limitations/implications: In this study, relatively few influencing factors such as welding current, voltage, speed and plate thickness are considered to analyze the inherent deformations in the T-welded joint. Also, these influencing factors are all within a certain range of parameters, which shows that only limited applicability can be provided. In addition, only in-plane inherent deformations are considered in this study, without considering the other two out-of-plane components of inherent deformations. Originality/value: This study can help to expand the understanding of the relationship between the inherent deformations and its influencing factors for a specific form of the welded joint, and can also provide basic data to supplement the inherent deformation database, thereby facilitating further researches on welding deformations for stiffened-panel structures in shipbuilding or steel bridges.